Backsliding understanding weakness of will - Mele, Alfred R., 1951- (Oxford : Oxford University Press, 2012)
People backslide. They freely do things they believe it would be best on the whole not to do - and best from their own point of view, not just the perspective of their peers or their parents. The aim of this book is to explain why that happens.
Includes bibliographical references and index.
Description based on online resource; title from PDF title page (viewed on Apr. 19, 2012).
Keywords: Akrasia